Developing a stone database for clinical practice. - Turney, B; Noble, J; Reynard, J (2011)
PURPOSE: Our objective was to design an intranet-based database to streamline stone patient management and data collection. MATERIALS AND METHODS: The system developers used a rapid development approach that removed the need for laborious and unnecessary documentation, instead focusing on producing a rapid prototype that could then be altered iteratively. By using open source development software and website best practice, the development cost was kept very low in comparison with traditional clinical applications. Information about each patient episode can be entered via a user-friendly interface. RESULTS: The bespoke electronic stone database removes the need for handwritten notes, dictation, and typing. From the database, files may be automatically generated for clinic letters, operation notes. and letters to family doctors. These may be printed or e-mailed from the database. Data may be easily exported for audits, coding, and research. CONCLUSIONS: Data collection remains central to medical practice, to improve patient safety, to analyze medical and surgical outcomes, and to evaluate emerging treatments. Establishing prospective data collection is crucial to this process. In the current era, we have the opportunity to embrace available technology to facilitate this process. The database template could be modified for use in other clinics. The database that we have designed helps to provide a modern and efficient clinical stone service.